القواعد القانونية للعمل المصرفي دراسة حالة المصارف السودانية - محمد النور, جودة ابراهيم (Gezira Journal of Economic and Social Sciences, 2022)
تعتبر المصارف إحدى الدعامات الأساسية في بناء الهيكل الاقتصادي للدولة ولقد زادت أهميتها  في العصر الحديث لمساهمتها في تطوير وتنمية مختلف قطاعات الاقتصاد القومي وخلق الجو المناسب والتربة الصالحة للتنمية الاقتصادية وتوفير الثقة وتدعيم الاستقرار لاقتصاديات البلاد. ومهما اختلف نظام الدولة السياسي والاقتصادي لا يمكنها الاستغناء عن وظائف المصارف لدورها الهام في تقدم الدول اقتصادياً واجتماعياً وسياسياً. ولكل ذلك خُصصت هذه الورقة للتعّرف على ماهية المصارف والنظام القانوني للأعمال المصرفية وذلك من خلال المباحث الآتية: التعّرف على ماهية الأعمال المصرفية ونزاعات المصارف، مع إبراز ِأسباب النزاعات المصرفية، كذلك هدف إلى بيان التكييف الفقهي للتحكيم في النزاعات المصرفية. اتبع الباحث في بحثه هذا المنهج الاستقرائي الوصفي، حيث يوثّق البحث للحقب التاريخية التي مرت بها المصارف، لإثراء دور المعارف والمكتبات بمدى أهمية دور المصارف، كما تم سرد النماذج والمراحل من المراجع والدراسات السابقة له. وبيان أوجه الدور الذي تؤديه المصارف. توصل البحث للعديد من النتائج والتي من أهمها: إن توفير الإطار التشريعي والتنظيمي الداعم، وتغيير استراتيجيات العمل داخل البنوك العربية يعمل على تحديث الجهاز المصرفي العربي، بروز ملامح الصيرفة الشاملة في البنوك من خلال القيام بأنشطة التـأجير التمـويلي، وتقـديم القروض المشتركة، تحديث أنظمة الدفع الالكتروني وغيرها. غير أن الغالب على طابع البنوك السودانية هو التقليدية. أوصى البحث بالآتي: العمل على تخفيف القيود والضوابط التي تفرض على المصارف بهدف التشجيع على قيام عدد من المصارف على مستوى البلد الواحد. إبراز الدور الرقابي على المصارف العامة والتجارية من قبل الدولة من خلال سياسات عبر البنك المركزي وتطوير التشريعات والتنظيمات المصرفية لتتمكن البنوك العربية من مزاولة أعمال مصرفية أكثر شمولية.   Legal Rules of Banking Business - A Case Study Of Sudanese Banks   Abstract          Banks are considered one of the main pillars in building the economic structure of the state, and their importance has increased in the modern era due to their contribution to the development and development of various sectors of the national economy, creating the appropriate atmosphere and suitable soil for economic development, providing confidence and strengthening stability for the country's economies. No matter how different the country's political and economic system is, it cannot dispense with the functions of banks for their important role in the economic, social and political progress of countries. For all of this, this paper is devoted to identifying the nature of banks and the legal system of banking through the following sections, so the research aims to: Identify the nature of banking and banking disputes, highlighting the causes of banking disputes, as well as a goal to indicate the jurisprudential adaptation of arbitration in banking disputes. In his research, the researcher followed this inductive and descriptive approach, where the research documents the historical eras that banks have gone through, to enrich the role of knowledge and libraries with the importance of the role of banks, and the models and stages of references and previous studies have been listed. And to clarify the aspects of the role played by banks. The research reached many results, the most important of which are: The provision of the legislative and regulatory framework supporting, and the change of work strategies within Arab banks works to modernize the Arab banking system, the emergence of the features of comprehensive banking in banks through the implementation of financial leasing activities, the provision of joint loans, the modernization of electronic payment systems and others. However, the nature of Sudanese banks is predominantly traditional. The research recommended the following: Work to ease restrictions and controls imposed on banks with the aim of encouraging the establishment of a number of banks at the level of a single country. Highlighting the supervisory role of public and commercial banks by the state through policies through the Central Bank and developing banking legislation and regulations to enable Arab banks to engage in more comprehensive banking business.